Impact of ambient heat exposure on pregnancy outcomes in low- and middle-income countries: A systematic review - Sohail Lakhani; Sobia Ambreen; Zahra Ali Padhani; Yusra Fahim; Sana Qamar; Salima Meherali; Zohra S Lassi (Women's Health)
Increasing global temperatures due to climate change have raised serious concerns regarding its potential impact on health outcomes. Pregnant women and their fetuses are among the most vulnerable groups being affected by these dramatic changes resulting in adverse outcomes for both the mother and the developing fetus. Evidence regarding heat-related pregnancy adversities in high-income countries is conclusive, however, such evidence is rare in low- and middle-income countries (LMICs). This review was conducted to bridge the knowledge gap by providing evidence-based insights into the specific repercussions of high heat exposures during pregnancy and its effect on birth outcomes in LMICs. A systematic review was conducted to assess the impact of high environmental or ambient temperatures on pregnancy outcomes (abortion, stillbirth, preterm birth, and low birthweight (LBW)) in LMICs. Electronic searches were conducted on MEDLINE, Embase, CINAHL, Web of Science, and Scopus. Observational studies published between 2010 and 2023 were included in the review. Screening of studies was done using Covidence software, data was extracted on Excel sheets and quality assessment was done using the National Institutes of Health’s National Heart, Lung, and Blood Institute tool. We included 11 studies. Four of six studies that included preterm births showed an association between heat and preterm births. Four of five studies reported an association between heat exposure and LBW. Three of four studies on stillbirths showed a significant association between heat exposure and stillbirths. One of the two studies that reported spontaneous abortion revealed a significant association of heat with abortion. Meta-analysis could not be performed due to the lack of homogeneity in defining heat exposure. Amongst the included studies, seven were categorized as “good” and four were categorized as “fair” on methodological quality. This study concluded that ambient temperature and heat exposure during pregnancy can impact birth outcomes such as preterm births, LBWs, abortions, and stillbirths in LMICs. Urgent action is imperative on both national and global scales to facilitate a comprehensive and definitive assessment of heat exposure in LMICs, enabling a deeper understanding of its repercussions on pregnant women. Longitudinal studies are paramount for confirming these associations and devising targeted interventions and strategies aimed at enhancing maternal and child health within LMIC contexts. Registration: PROSPERO ID: CRD42023449173.